Reabsorción radicular externa asociada al tratamiento ortodóncico: revisión de la literatura (2020)
External root resorption (RRE) is defined as a destruction of the cement or the dentin due to cementotic or osteoclastic activity, resulting in a shortening of the root when orthodontic force is applied. Approximately 80% of the patients present some degree of resorption.  This condition has great variability, and its etiology is multifactorial, so this literature review aims to provide information of root resorption and its predisposing factors in order to prevent or intervene in a timely manner this undesired effect. To carry out this study, databases as Pubmed, Scielo, Wiley, Elsevier were used, having as a search limit articles published between 2010 and 2020, with the exception of three studies, one from 2005, from 2007 and the other one from 2009, which provided highly relevant information about risk factors of root resorption. External root resorption is a prevalent complication and there is currently no consensus to manage this phenomenon, which is why systematic studies are needed to provide more reliable evidence so that both orthodontists and other specialists have more knowledge of the subject and complications are avoid both in the diagnosis such as during treatment when performing tooth movements.